Chlamydial entry involves TARP binding of guanine nucleotide exchange factors. - B Josh Lane; Charla Mutchler; Souhaila Al Khodor; Scott S Grieshaber; Rey A Carabeo (PLoS Pathogens)
Chlamydia trachomatis attachment to cells induces the secretion of the elementary body-associated protein TARP (Translocated Actin Recruiting Protein). TARP crosses the plasma membrane where it is immediately phosphorylated at tyrosine residues by unknown host kinases. The Rac GTPase is also activated, resulting in WAVE2 and Arp2/3-dependent recruitment of actin to the sites of chlamydia attachment. We show that TARP participates directly in chlamydial invasion activating the Rac-dependent signaling cascade to recruit actin. TARP functions by binding two distinct Rac guanine nucleotide exchange factors (GEFs), Sos1 and Vav2, in a phosphotyrosine-dependent manner. The tyrosine phosphorylation profile of the sequence YEPISTENIYESI within TARP, as well as the transient activation of the phosphatidylinositol 3-kinase (PI3-K), appears to determine which GEF is utilized to activate Rac. The first and second tyrosine residues, when phosphorylated, are utilized by the Sos1/Abi1/Eps8 and Vav2, respectively, with the latter requiring the lipid phosphatidylinositol 3,4,5-triphosphate. Depletion of these critical signaling molecules by siRNA resulted in inhibition of chlamydial invasion to varying degrees, owing to a possible functional redundancy of the two pathways. Collectively, these data implicate TARP in signaling to the actin cytoskeleton remodeling machinery, demonstrating a mechanism by which C.trachomatis invades non-phagocytic cells.